2022
DOI: 10.1155/2022/6041827
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Oral Tranexamic Acid on the Blood Transfusion Rate and the Incidence of Deep Vein Thromboembolism in Patients after TKA

Abstract: Purpose. To explore the effect of oral tranexamic acid treatment on the blood transfusion rate and the incidence of deep vein thromboembolism after total knee arthroplasty (TKA). Methods. 90 patients undergoing TKA admitted to First People’s Hospital of Changshu City from January 2019 to January 2020 were selected and randomized into the control group and the experimental group accordingly (45 cases in each group). The control group intravenously received 20 mL/kg tranexamic acid before the incision was closed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%